STRATEGI PEMASARAN PRODUK GRIYA HASANAH PADA BANK SYARIAH INDONESIA - Muhammad Fadhil Abdillah, (2021)
Banking in Indonesia in the modern era today, has many types of business fields. One of them is to provide services to help people own a home by providing loans or financing. But the amount of competition requires banks to implement good marketing strategies to be able to attract people using their services. A well-planned marketing strategy, will make it easier for banks to reach a target. Banks must have the advantages of services offered to the public so that people choose to use the services of banks to own a home, including Bank Syariah Indonesia. As a bank that uses sharia principles, Bank Syariah Indonesia provides financing to people who want to own a home by using an agreement in accordance with sharia principles, namely murabahah agreement in a product called Griya Hasanah. This research aims to find out the marketing strategy conducted by Bank Syariah Indonesia in marketing Griya Hasanah products. The source used as analysis material is to use qualitative analysis method by conducting interviews to several employees of Bank Syariah Indonesia and collecting information from several sources. The result of this study is Bank Syariah Indonesia using 4P marketing mix strategy consisting of product, price, place, and promotion. The marketing strategy conducted by Bank Syariah Indonesia has a positive impact on the target of achieving Griya Hasanah products.